Respuesta :
[tex]( \frac{r}{s} )(6)= \frac{r(6)}{s(6)} [/tex]
r(6)=3(6)-1=18-1=17
s(6)=2(6)+1=12+1=13
[tex]( \frac{r}{s} )(6)= \frac{r(6)}{s(6)}= \frac{17}{13} [/tex]
r(6)=3(6)-1=18-1=17
s(6)=2(6)+1=12+1=13
[tex]( \frac{r}{s} )(6)= \frac{r(6)}{s(6)}= \frac{17}{13} [/tex]
Answer:
[tex]\frac{r}{s}(6)=\frac{17}{13}[/tex]
Step-by-step explanation:
Given : [tex]r(x)=3x-1[/tex]
[tex]s(x)=2x+1[/tex]
To Find: (r/s)(6)
Solution:
[tex]r(x)=3x-1[/tex]
[tex]s(x)=2x+1[/tex]
So, [tex]\frac{r}{s}(x)=\frac{3x-1}{2x+1}[/tex]
Substitute x =6
So, [tex]\frac{r}{s}(6)=\frac{3(6)-1}{2(6)+1}[/tex]
[tex]\frac{r}{s}(6)=\frac{17}{13}[/tex]
Hence [tex]\frac{r}{s}(6)=\frac{17}{13}[/tex]